1981
DOI: 10.1099/00221287-124-1-109
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Properties of   and   Pili from Variants of Neisseria gonorrhoeae P9

Abstract: The a and p type pili produced by variants of Neisseria gonorrhoeae P9 were isolated and characterized. The two types of pili showed clear differences in morphology, buoyant density (a, 1.292 g ml-l; p, 1.282 g ml-I) and isoelectric point (a, PI 5.2; p, PI 4.3). Amino acid analysis of a and / 3 pili showed that their overall composition was similar with the exception that p pili had a higher content of glutamate and alanine residues. A high degree of structural homology was seen in two-dimensional peptide maps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…These results are not consonant with Pearce and Buchanan's (3) finding that whole, iodinated pill bind buccal and endocervical cells equally well. This discrepancy might be explained by the observation of Lambert et al (29) that some gonococcal pill appear to bind different receptor compounds. Alternatively, binding studies conducted with undenatured pill may lack specificity because the filaments readily associate with hydrophobic surfaces including glass, plastic, latex beads (48), and synthetic lipid bilayers (G. Schoolnik, unpublished observation).…”
Section: Discussionmentioning
confidence: 98%
“…These results are not consonant with Pearce and Buchanan's (3) finding that whole, iodinated pill bind buccal and endocervical cells equally well. This discrepancy might be explained by the observation of Lambert et al (29) that some gonococcal pill appear to bind different receptor compounds. Alternatively, binding studies conducted with undenatured pill may lack specificity because the filaments readily associate with hydrophobic surfaces including glass, plastic, latex beads (48), and synthetic lipid bilayers (G. Schoolnik, unpublished observation).…”
Section: Discussionmentioning
confidence: 98%
“…If the identification of two pilins by SDS-PAGE and two morphologic types by electron microscopy are related, meningococci may elaborate pilus variants that are homopolymers composed ofpilins of different molecular mass. These variants might also exhibit different receptor-binding specificities analogous to the pili types produced by the P-9 strain of N. gonorrhoeae (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies utilising peptide mapping have shown that a and/3 pilins have regions of considerable structural homology and differ only in a 341 small region on the molecule [10]. Previous studies utilising peptide mapping have shown that a and/3 pilins have regions of considerable structural homology and differ only in a 341 small region on the molecule [10].…”
Section: Discussionmentioning
confidence: 99%